Respuesta :
Answer:
(6, - 3 )
Step-by-step explanation:
Given the 2 equations
2x + 5y = - 3 → (1)
2x + 2y = 6 → (2)
Subtracting (1) from (2) term by term will eliminate the x- term
(2x - 2x) + (2y - 5y) = 6 - (- 3), that is
- 3y = 9 ( divide both sides by - 3 )
y = - 3
Substitute y = - 3 in either of the 2 equations and solve for x
Substituting y = - 3 in (1)
2x + 5(- 3) = - 3
2x - 15 = - 3 ( add 15 to both sides )
2x = 12 ( divide both sides by 2 )
x = 6
Solution is (6, - 3 )
Answer: x = 6 and y = -3
Step-by-step explanation: What we have in this question is a pair of simultaneous equations,
2x + 5y = -3 ———(1)
2x + 2y = 6 ———(2)
We shall use the elimination method to solve this since none of the variables has a coefficient of 1. We multiply equation (1) by 2 and multiply equation (2) by 5 {to eliminate the y variable). So we now have,
2x + 5y = -3 ——— x2
2x + 2y = 6 ——— x5
4x + 10y = -6 ———(3)
10x + 10y = 30 ——(4)
Subtract equation (3) from equation (4)
10x - 4x +(10y - 10y) = 30 - (-6)
6x = 30 + 6
6x = 36
Divide both sides of the equation by 6
x = 6
Having calculated that x = 6, substitute for the value of x into equation (1)
2x + 5y = -3
2(6) + 5y = -3
12 + 5y = -3
Subtract 12 from both sides of the equation
5y = -3 - 12
5y = -15
Divide both sides of the equation by 5
y = -3
Therefore x equals 6 and y equals -3